Comparative values of prairie hay and sorghum grain for calves - Smith, E.F.; Richardson, D.; Perry, H.B. (Kansas Agricultural Experiment Station, 2011)
This test was to determine if sorghum grain could completely replace prairie hay in a ration for calves being fed for limited growth. Intake of grain was restricted to supply approximately the same amount of energy consumed by calves fed hay free choice.
Keywords: Beef; Prairie hay; Sorghum grain; Nutrient intake